2014
DOI: 10.1039/c3nr05177c
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of nanoscale domain purity and size on charge transport and recombination dynamics in polymer solar cells

Abstract: Charge transport and bimolecular recombination dynamics were correlated with nanomorphology in polymer solar cells. The morphology of poly(diketopyrrolopyrrole-terthiophene) (PDPP3T) and phenyl-C61-butyric acid methyl ester (PC60BM) blend films was modified using different solvent additives namely 1-chloronaphthalene (CN), 1,8-diiodooctane (DIO) and 1,8-octanedithiol (ODT) and their role on steady state and transient optoelectronic properties was investigated. The energy filtered transmission electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 35 publications
(40 reference statements)
3
51
0
Order By: Relevance
“…All observations were made using a commercial Agilent 5500 scanning probe microscope. The imaging was done in tapping mode using Si cantilevers (Budget Sensors TAP 300 Al; Innovative Solutions Bulgaria Ltd., Sofia, Bulgaria) with the AFM tip having resonant frequency around 300 kHz (Venkatesan et al, 2014). The membrane sample was mounted on the sample stage by sticking 4 corners of the membrane to the stage with scotch tape.…”
Section: Microscopic Observations Of Membrane Biofilmsmentioning
confidence: 99%
“…All observations were made using a commercial Agilent 5500 scanning probe microscope. The imaging was done in tapping mode using Si cantilevers (Budget Sensors TAP 300 Al; Innovative Solutions Bulgaria Ltd., Sofia, Bulgaria) with the AFM tip having resonant frequency around 300 kHz (Venkatesan et al, 2014). The membrane sample was mounted on the sample stage by sticking 4 corners of the membrane to the stage with scotch tape.…”
Section: Microscopic Observations Of Membrane Biofilmsmentioning
confidence: 99%
“…Venkatesan et.al. 17 compared the effects of several additives on the morphology of the active layer. Results showed that CN and DIO additives gave an optimal morphology, which helped to increase the overall efficiency of BHJ solar cells.…”
Section: Effect Of Processing Parameters and Morphology On Solar Cellmentioning
confidence: 99%
“…7. 17 The EFTEM analysis gave deep insight into the local domain of both donor and acceptor phases. The donor and acceptor mapping for each type of film was compared.…”
Section: Effect Of Processing Parameters and Morphology On Solar Cellmentioning
confidence: 99%
See 2 more Smart Citations